Sedimentation environment during deglaciation and Holocene in Southern Sentralbanken, Barents Sea - Hultin, Monica (UiT Norges arktiske universitet, 2016)
Grounding zone wedges and ridges throughout the Barents Sea gives good spatial constraints of the Late Weichselian deglaciation of the Barents Sea, however, little is known about Late Weichselian ice dynamics in the Central Barents Sea, primarily due to a lack of data. The study is carried out south of Sentralbanken in Sentralbankrenna which was likely an important source area feeding the Bjørnøyrenna ice stream during the glaciation and throughout the deglaciation. Previous studies have documented a network of tunnel valleys (Bjarnadottir et al., 2012; 2014), and has for the first time provided evidence for abundant meltwater activity in this area. Understanding how ice retreated through this trough is important for reconstructing behaviour of the Bjørnøyrenna Ice stream and the Barents Sea Ice Sheet as a whole. Four sediments gravity cores were retrieved and investigated by lithological logs, physical properties, XRF scan, X-ray and particle size analyser to reveal the sedimentary processes dominating Sentralbankrenna from the deglaciation throughout Holocene. Close to 200 samples were collected throughout the cores allowing detailed investigation of grain size distribution. Sentralbankrenna serves as a funnel for sediments coming from North, Northeast, East and Southeast, and an analysis of the sediments deposited in this area will therefore help to understand the pattern of ice flow and sediment transport. The study reveals a deglacial environment dominated by IRD, meltwater plumes and suspensions settling. Foraminifera of different age and a belemnite found in the deeper part of the core suggest the lamination is a product of reworking and transport of sediments with origin in the northern Barents Sea. After the deglaciation a homogenous sediments pack reveals a change in deposition and transport mechanism, indicating a warmer climate and sedimentation dominated by bottom currents and reworking of sediments. Key words: Sediments, Sediment environment, sediment processes, Holocene, Deglaciation, Central ...